OHS, Organizational Culture, and Employee Engagement in Production Performance: K3, Budaya Organisasi, dan Employee Engagement pada Kinerja Produksi - Prahadi , Fajar Krisna; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2025)
General Background: Employee performance in industrial production activities is closely related to workplace safety and human resources management. Specific Background: Production performance in PT Japfa Comfeed Indonesia showed fluctuations and reduced achievement, which may be associated with safety, working culture and employee motivation. Knowledge Gap: Previous studies reported inconsistent findings regarding the relationship between occupational safety, organizational culture, employee engagement and performance. Aims: This research examines the significance of occupational health and safety, organizational culture and employee engagement toward employee performance. Results: Using multiple linear regression with 78 respondents, all three variables significantly and positively contribute to employee performance, both partially and simultaneously. Novelty: This study reassesses previous inconsistent studies by presenting empirical evidence from the production environment of PT Japfa Comfeed Indonesia. Implications: Findings provide practical recommendations for strengthening workplace safety, organizational culture and employee involvement in industrial settings. Highlights:• Positive contribution of K3• Organizational culture reinforcement• Engagement role in production performance Keywords: Occupational Health and Safety, Organizational Culture, Employee Engagement, Employee Performance, Production